Peningkatan Kreativitas dan Inovasi Mahasiswa dalam Pembuatan Lilin Aromaterapi Berbasis Kewirausahaan - Nafi’ah Alifia Anindita Susilo; Anggit Dyah Kusumastuti (Kegiatan Positif : Jurnal Hasil Karya Pengabdian Masyarakat, 2025)
This activity is a form of community service aimed at enhancing students’ creativity and innovation through hands-on training in making aromatherapy candles based on entrepreneurial principles. In this program, students received direct guidance on the process of creating aromatherapy candles, including selecting materials, blending scents, and molding the final product. Beyond technical skills, students were introduced to basic entrepreneurial concepts to encourage creative and innovative thinking in developing valuable products. Through a practical and interactive approach, this activity successfully improved students’ creative skills and built their confidence in expressing new ideas. The results show an increase in students’ understanding of the importance of innovation in entrepreneurial endeavors. Overall, this program had a positive impact on shaping students’ entrepreneurial spirit and enhancing their ability to think creatively, serving as valuable preparation for future challenges.